The effect of jicama (Pachyrhizus erosus L.) starch on the properties and probiotic potential of L. plantarum SN13T fermented milk - Melia, Sri; Juliyarsi, Indri; Setiawan, Rizki D; Aritonang, Salam N; Alzahrah, Hurriya; Supandil, Doni (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study investigated the application of Jicama starch (Pachyrhizus erosus L.) as a stabilizing agent to enhance the longevity and integrity of fermented milk. Materials and Methods: Lactobacillus plantarum SN13T (6 gm/100 ml) and Jicama starch (2 gm/100 ml) were added into pasteurized milk (65°C, 30 min) and then incubated under anaerobic conditions at 37°C for 18 h. The fermented milk was stored at 4°C. The evaluation on proximate composition, pH, titratable acidity (TA), viscosity, water holding capacity (WHC), syneresis, total lactic acid bacteria (LAB), and hedonic sensory evaluation was conducted at 1, 7, 14, 21, and 28 days of storage. Results: Throughout the storage period, fermented milk enriched with Jicama starch significantly (p < 0.05) increased pH, TA, population dynamics of LAB, viscosity, WHC, and syneresis. It effectively sustained WHC and mitigated syneresis, thus ensuring the preservation of vital product quality. Furthermore, the quantity of LAB within the fermented milk consistently met the probiotic threshold of 84.50 × 108 CFU/ml. The hedonic sensory evaluation results indicated that fermented milk showed consistent sensory attributes throughout storage, except for overall acceptance, which declined on day 28. Conclusion: The addition of Jicama starch revealed a promising health probiotic product, presenting a viable avenue for delivering probiotic benefits to consumers while maintaining the palatability and efficacy of the product. Adv. Vet. Anim. Res., 11(2): 317-322, June 2024 http://doi.org/10.5455/javar.2024.k779